Design and formation of workforce skills for machine tool assembly. Issue 1 (2015) - Mori, Masahiko; Ota, Keiichi; Matsubara, Atsushi; Mizuyama, Hajime
Abstract The demand for machine tools is rapidly changing and the assembly of them is dependent on human workforce. To achieve efficient machine tool assembly, design and formation of workforce skills are required. This paper presents an approach of design and formation of workforce skills for machine tool assembly using simulations. A simulation model is developed based on the investigation at an actual machine tool shop-floor and several workforce skill formations are applied to the simulation. Effects of forming skilled workforce are examined and an analysis of improvement in the level of skills in actual examples is presented.